Why Do Firms Pay for Liquidity Provision in Limit Order Markets? - Johannes A. Skjeltorp; Bernt Arne Ødegaard (Norges Bank, 2010)
In recent years, a number of electronic limit order markets have reintroduced market makers for some securities (Designated Market Makers). This trend has mainly been initiated by financial intermediaries and listed firms themselves, without any regulatory pressure. In this paper we ask why firms are willing to pay to improve the secondary market liquidity of their shares. We show that a contributing factor in this decision is the likelihood that the firm will interact with the capital markets in the near future, either because they have capital needs, or that they are planning to repurchase shares. We also find some evidence of agency costs associated with the initiation of a market maker agreement as the probability of observing insider trades increases when liquidity improves.
hdl:11250/2497451
Keywords: G10; G20; 330; market liquidity; corporate finance; designated market makers; insider trading